Material de enseñanza virtual sobre el reconocimiento del cuerpo y el ecosistema, en los niños con síndrome de Down (2021)
This project was designed as a didactic strategy for teaching and learning the body and ecosystem recognition. It focuses on living environment approach that surrounds children with Down syndrome, to allow them to be part of a meaningful virtual educational process. The main objective is to design a virtual didactic material for children with Down syndrome, which helps to strengthen their knowledge around biology. The Pandemic has caused many children left school because they do not have enough technological resources, and teachers do not have virtual tools to be able to support them from the virtuality. It is important to renew the pedagogical practices, for this purpose an interactive digital booklet is designed that allows the child, teachers, and family members to continue with the learning process, helping to strengthen meaningful learning in the biology area.